2013
DOI: 10.1080/17441692.2013.829511
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary assessment of financial stability, efficiency, health systems and health outcomes using performance-based contracts in Belize

Abstract: Over the last 10 years, Belize has implemented a National Health Insurance (NHI) program that uses performance-based contracts with both public and private facilities to improve financial sustainability, efficiency and service provision. Data were collected at the facility, district and national levels in order to assess trends in financial sustainability, efficiency payments, year-end bonuses and health system and health outcomes. A difference-in-difference approach was used to assess the difference in techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“… Are there potential conflicts of interest? Bowser (2013) [ 19 ] No Status quo (traditional salaries and line-item budgets). 2006 to 2010 No clear description of the included and omitted costs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Are there potential conflicts of interest? Bowser (2013) [ 19 ] No Status quo (traditional salaries and line-item budgets). 2006 to 2010 No clear description of the included and omitted costs.…”
Section: Resultsmentioning
confidence: 99%
“…The seven articles examined the impact of PBF programs over different time periods. Gok & Altmdag [ 18 ]’s study ranges from 2001–2008; Bowser et al [ 19 ] and Sabri et al [ 20 ]’s study cover a four-year time period; and Zeng et al [ 21 ], Basinga et al [ 16 ], Rusa et al [ 22 ], and Soeters et al [ 23 ] report change over a two year period. From the studies in this review, little is known about how the relation between PBF costs and outcomes in LMICs evolves over the long term.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Health worker shortages are a commonly acknowledged problem in Africa but P4P can be expected to improve the supply of health workers. A study in Belize found an increase in nurse density resulting from a national health insurance scheme with inbuilt performance contracts [ 17 ]. Health workers low satisfaction with salaries and employment benefits has been reported in other studies undertaken in Tanzania [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…4 There are only a few in-country studies that have examined the impact on health outcomes from pay-for-performance in upper-middle-income countries. 11,56 The results from some high-income countries, like England, do suggest that pay-for-performance can have an impact on mortality in the hospital setting. 57 The significant impact of community-based health insurance on infant and under-five mortality and association with reduced maternal mortality is important and encouraging.…”
Section: Discussionmentioning
confidence: 99%